Recording CSF Pressure with a Transducer-Tipped Wire in an Animal Model of Chiari I - Turk, A.; Iskandar, B.J.; Haughton, V.; Consigny, D. (American Journal of Neuroradiology, 2006)
SUMMARY: In dogs, a wire with a pressure-sensitive transducer was inserted percutaneously into the subarachnoid space and manipulated under fluoroscopic monitoring in the posterior fossa or upper cervical spinal canal. Pressure recordings from the wire showed fluctuations in pressure corresponding to the cardiac cycle. When a balloon was distended in the foramen magnum, maximum and minimum pressures increased. Continuous monitoring of CSF pressure remote from the site of cannulation was feasible with a wire-based pressure transducer.